1997
DOI: 10.1073/pnas.94.15.8132
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of the WT1 Wilms tumor suppressor gene in human breast cancer

Abstract: The product of the WT1 Wilms tumor suppressor gene controls the expression of genes encoding components of the insulin-like growth factor and transforming growth factor ␤ signaling systems. The role of these growth factors in breast tumor growth led us to investigate possible WT1 gene expression in normal and cancerous breast tissue. WT1 was detected by immunohistochemistry in the normal mammary duct and lobule, and the patterns of expression were consistent with developmental regulation. In a survey of 21 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
154
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 45 publications
10
154
2
Order By: Relevance
“…Silberstein et al (1997) reported loss of WT1 expression in breast tumors, and Zhang et al (2003) reported observations consistent with a tumor suppressor role. In contrast, our group reported overexpression of WT1 in breast tumors as compared with normal mammary epithelium (Loeb et al, 2001), and Zapata- Benavides et al (2002) reported data consistent with an oncogenic role.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Silberstein et al (1997) reported loss of WT1 expression in breast tumors, and Zhang et al (2003) reported observations consistent with a tumor suppressor role. In contrast, our group reported overexpression of WT1 in breast tumors as compared with normal mammary epithelium (Loeb et al, 2001), and Zapata- Benavides et al (2002) reported data consistent with an oncogenic role.…”
Section: Discussionmentioning
confidence: 97%
“…We investigated the function of individual WT1 isoforms expressed in isolation, but primary breast tumors frequently express multiple isoforms (Silberstein et al, 1997;Loeb et al, 2001). Thus, the net effect of WT1 will probably reflect a balance of the effects of different isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, immunohistochemical data on WT1 expression in other types of cancers are either lacking or conflicting. 17,18,[21][22][23][24] As for staining patterns, cytoplasmic staining has been regarded as nonspecific and not been counted as positive in most previous reports. Therefore, the cytoplasmic staining of WT1 had not been evaluated in most types of tumors until now.…”
mentioning
confidence: 99%